Hitting the material rail: An exploration of the comparison between Alloy Steel and AISI 1020 - Rendy Satriawan; Zhazira A. Baltabekova (Innovation in Engineering, 2024)
The rail track is a component that directly interfaces with the wheels. Generally, rail tracks serve as the foundation for trains, trams, and similar vehicles, bearing the friction and pressure from the wheels. Rail tracks have the potential for cracking and breaking due to various loads. Many studies have investigated the factors causing rail track fractures. This article employs the Finite Element Analysis (FEA) method using Solidworks research license software. In this simulation, two rail tracks with different materials, AISI 1020 and Alloy Steel, are numerically studied using Solidworks software to determine the most effective material for mitigating the risk of rail track fractures. The fracture risk is then calculated based on the material's fracture strength. The simulation results indicate that the fracture risk of rail tracks using Alloy Steel is lower than that of AISI 1020, thus recommending Alloy Steel as the more suitable material for rail tracks.